Integration of Constructivist Pedagogy and ICT Tools to Enhance Learning Outcomes - Diyal, Suresh Bahadur (Educational Journal, 2024)
The integration of constructivist pedagogy and Information and Communication Technology (ICT) tools offers a transformative approach to modern education, fostering active, learner-centered knowledge construction through collaboration, problem-solving, and real-world application. Rooted in the theories of Piaget and Vygotsky, constructivism aligns seamlessly with ICT tools such as interactive simulations, collaborative platforms, and adaptive learning software, which facilitate personalized and experiential learning. However, challenges such as inadequate teacher training, infrastructure gaps, and socio-cultural resistance hinder effective implementation, particularly in developing contexts like Nepal. This study employs a systematic literature review to analyze the intersection of constructivist pedagogy and ICT, drawing from Nepalese education policies (NNEPC 1954 to NCF 2019) and global academic literature (1971-2023). Findings expose that ICT tools operationalize core constructivist principles such as Vygotsky’s Zone of Proximal Development (ZPD), More Knowledgeable Other (MKO), and scaffolding through dynamic, technology-mediated learning environments. The study concludes with actionable recommendations, emphasizing policy alignment, equitable resource allocation, and scaffolded ICT integration to bridge the gap between theory and practice. By strategically combining constructivist pedagogy with ICT, educators can cultivate higher-order critical thinking, creativity, communication, collaboration skills, and lifelong learning competencies.